2020
DOI: 10.1186/s12964-020-00606-w
|View full text |Cite
|
Sign up to set email alerts
|

AKT/FOXO1 axis links cross-talking of endothelial cell and pericyte in TIE2-mutated venous malformations

Abstract: Background: Venous malformations (VMs), most of which associated with activating mutations in the endothelial cells (ECs) tyrosine kinase receptor TIE2, are characterized by dilated and immature veins with scarce smooth muscle cells (SMCs) coverage. However, the underlying mechanism of interaction between ECs and SMCs responsible for VMs has not been fully understood. Methods: Here, we screened 5 patients with TIE2-L914F mutation who were diagnosed with VMs by SNP sequencing, and we compared the expression of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…3A). Although Tie2 mutation is commonly recognized as an abnormally activated mutation [13,20], the sequencing results showed that the Tie2 mutation background induced the downregulation of 126 genes in pulmonary vascular malformations, and more than 62 genes were upregulated (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). Although Tie2 mutation is commonly recognized as an abnormally activated mutation [13,20], the sequencing results showed that the Tie2 mutation background induced the downregulation of 126 genes in pulmonary vascular malformations, and more than 62 genes were upregulated (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Under the in uence of TIE2 mutation in ECs, most studies have focused on the recruitment de ciency of VSMCs [7,12]. However, few investigations have been carried out to emphasize the alteration of the contractile function and strength of VSMCs, which may also play an important role in the VM formation process [13].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, it has been shown that all TEK ( TIE2 ) mutations lead to ligand-independent hyperphosphorylation of the receptor and a permanent activation of the PI3K/AKT/mTOR signaling pathway, the effect being stronger in the presence of a double mutation, compared to the presence of a single mutation of the TEK gene [ 39 , 40 ].…”
Section: Vascular Anomalies: Pi3k/akt/mtor Signaling Pathways (Pikopa...mentioning
confidence: 99%
“…Mutations in the TEK/ TIE2 gene significantly impede the ability of ECs to produce PDGFB. Downregulation of PDGFB depends on AKT phosphorylation (FOXO1-Mediated Activation of AKT) [ 40 ]. Si et al [ 40 ] showed that the TEK L9144F mutation acts through the AKT/FOXO1/PDGFB pathway to produce VMs.…”
Section: Vascular Anomalies: Pi3k/akt/mtor Signaling Pathways (Pikopa...mentioning
confidence: 99%
See 1 more Smart Citation